Find The Equation Of The Tangent Line To The Curve

Anonymous

From: -
Posts: -
Votes: -
Find the equation of the tangent line to the curve (x^2 +y^2)^2 = 4x^2yat the point (1,1).

 

Answer No.1

Anonymous

From: -
Posts: -
Votes: -
I think that y = is not meant to be there. So I'm going to answer the question "Find the equation of the tangent line to the curve x + 4xy + y = 13 at the point (2, 1)." Are you familiar with implicit differentiation? If we differentiate both sides of this equation with respect to x, the first term gives 2x we need the product formula to differentiate 4xy: It's 4*derivative of x * y + 4*x*derivative of y = 4y + 4xy' using y' to denote dy/dx we use the chain rule to differentiate y: It's 2y*y'. And the derivative of 13 is 0. So we get 2x + 4y + 4xy' +2yy' = 0 Therefore 4xy' + 2yy' = -2x - 4y 2(2x + y)y' = -2(x + 2y) y' = -(x + 2y)/(2x + y) after cancelling the common factor 2. At the point (2, 1), y' = -(2 + 2)/(4 + 1) i.e. gradient of tangent = -4/5 Using y - y1 = m(x - x1) we get the equation of the tangent y - 1 = -(4/5)(x - 2) 5y - 5 = -4x + 8 4x + 5y - 13 = 0 THERE IS A SHORTCUT: For equations like this, containing only first and second powers of x and y, we can get the equation of the tangent at the point x, y by replacing x in the equation by xx1, y by yy1, x by (x + x1)/2, y by (y + y1)/2, and xy by (xy1 + x1y)/2. In this case, that gives 2x + 2(x +2y) + y = 13 leading to the same equation as found above. CONFIRMATION. If you solve the simultaneous equations x + 4xy + y = 13 and 4x + 5y - 13 = 0 by eliminating y, we get the solution (x - 2) = 0, the double root confirming that the line is a tangent to the curve at x = 2

Answer No.2

Anonymous

From: -
Posts: -
Votes: -
Slope at (1,1) 2(x^2+y^2)(2x+2y dy/dt)=8xy+4x^2 dy/dt =>2(2)(2+2dy/dt)=8+4dy/dt =>dy/dt=0 so the slope of tangent -infinity equation of tangent=> (X-1=0)

Answer No.3

EliteMath1

From: US
Posts: 5
Votes: 20
(x^2+y^2)*(2x+2ydy/dx)=8*x =4+4dy/dx=8 dy/dx=1 y-1=1*(x-1) y=x

Answer No.4

Anonymous

From: -
Posts: -
Votes: -
For equations like this, containing only first and second powers of x and y, we can get the equation of the tangent at the point x, y by replacing x in the equation by xx1, y by yy1, x by (x + x1)/2, y by (y + y1)/2, and xy by (xy1 + x1y)/2. In this case, that gives 2x + 2(x +2y) + y = 13 leading to the same equation as found above. CONFIRMATION. If you solve the simultaneous equations x + 4xy + y = 13 and 4x + 5y - 13 = 0 by eliminating y, we get the solution (x - 2) = 0, the double root confirming that the line is a tangent to the curve at x = 2

Answer No.5

Anonymous

From: -
Posts: -
Votes: -
Slope at (1,1) 2(x^2+y^2)(2x+2y dy/dt)=8xy+4x^2 dy/dt =>2(2)(2+2dy/dt)=8+4dy/dt =>dy/dt=0 so the slope of tangent -infinity equation of tangent=> (X-1=0)

Answer No.6

Anonymous

From: -
Posts: -
Votes: -
(x^2+y^2)*(2x+2ydy/dx)=8*x =4+4dy/dx=8 dy/dx=1 y-1=1*(x-1) y=x

Answer No.7

Anonymous

From: -
Posts: -
Votes: -
Answer: y =1 we need two independent information in order to determine the tangent line, in this problem, ==>we have (1)a point that the tangent line passes: (1,1) ->(x0, y0) ==>we can find (2) the slope of the tangent line by computing y' at (1,1)->m then, we just substitute these in y = y0 + m (x - x0) = 1 + m(x -1) = 1-m + mx ---------------- let us find (2): use implicit differentiation to find y': 2(x2 +y2)(2x + 2yy') = 4(2xy + x2y') =>(x2 +y2)(x + yy') = (2xy + x2y') =>(x2 +y2)(x) - 2xy = x2y' - (x2 +y2)(yy') =>(x2 +y2)(x) - 2xy = {x2 - (x2 +y2)y} y' =>y' = {(x2 +y2)(x) - 2xy} / {x2 - (x2 +y2)y} to find the slope at (1,1), we substitute: y' = {(12 +12)(1) - 2(1)(1)} / {12 - (12 +12)(1)} y' = {2 - 2} / {1 - 2} = 0 -------------------- y = 1-m + mx = 1 y = 1

Answer No.8

DedicatedRoger

From: US
Posts: 33
Votes: 33
Given that:slope at (1,1) now differentiating both side of the givencurve equation: 2(x^2+y^2)(2x+2y dy/dt)=8xy+4x^2 dy/dt =>2(2)(2+2dy/dt)=8+4dy/dt =>dy/dt=0 so the slope of tangent -∞ equation of tangent is (X-1=0)

Answer No.9

Anonymous

From: -
Posts: -
Votes: -
**** SIMPLEST WAY ***** For equations like this, containing only first and second powers of x and y, we can get the equation of the tangent at the point x, y by replacing x in the equation by xx1, y by yy1, x by (x + x1)/2, y by (y + y1)/2, and xy by (xy1 + x1y)/2. In this case, that gives 2x + 2(x +2y) + y = 13 4x+5y-13=0

Your Comment/Solution

Post As: Anonymous [Change]
Enter